Metabolite analysis of Arabidopsis CYP79A2 overexpression lines reveals turnover of benzyl glucosinolate and an additive effect of different aldoximes on phenylpropanoid repression. (2nd November 2021) - Perez, Veronica C.; Dai, Ru; Block, Anna K.; Kim, Jeongim
ABSTRACT: Indole-3-acetaldoxime (IAOx) and phenylacetaldoxime (PAOx) are precursors for the growth hormones indole-3-acetic acid (IAA) and phenylacetic acid (PAA) and the defense compounds glucosinolates in Brassicales. Our recent work has shown that Arabidopsis transgenic lines overexpressing AtCYP79A2, a PAOx-production enzyme, accumulate the PAOx-derived compounds benzyl glucosinolate and PAA. Here we report that they also accumulate the benzyl glucosinolate hydrolysis products benzyl isothiocyanate and benzyl cyanide, which indicates that the turnover of benzyl glucosinolate can occur in intact tissues. Myrosinases or β-glucosidases are known to catalyze glucosinolate breakdown. However, transcriptomics analysis detected no substantial increase in expression of known myrosinases or putative β-glucosidases in AtCYP79A2 overexpressing lines. It was previously shown that accumulation of aldoximes or their derivatives represses the phenylpropanoid pathway. For instance, ref2 mutant having a defect in one of the aldoxime catabolic enzymes decreases phenylpropanoid production. Considering that AtCYP79A2 is not expressed in most organs under optimal growth condition, ref2 accumulates aliphatic aldoximes but not PAOx. Interestingly, overexpression of AtCYP79A2 in ref2 resulted in a further decrease in sinapoylmalate content compared to ref2 . This indicates that accumulation of PAOx has an additive effect on phenylpropanoid pathway suppression mediated by other aldoximes.